Penile implants: a look into the future - Rodriguez, Katherine M.; Kohn, Taylor P.; Davis, Anthony B.; Hakky, Tariq S. (Translational Andrology and Urology, 2017)
nflatable penile prosthesis (IPP) has been around since the 1970’s as a durable and one-time cure for erectile dysfunction (ED). For the past 40 years, many changes have been made to make the device better and currently IPP boasts a high percentage of long-term patient satisfaction. The next paradigm shift in IPP treatment for ED is upon us. Funding for ED related medications and devices has been a hot topic in health policy over the last 10 years. This suggests that the device must improve and patient advocacy and education must increase for IPP to remain as a viable solution for ED. In this paper, we conduct a literature search for innovations in IPP and argue that IPP must constantly improve to compete with oral, injectable, shockwave, and potentially gene therapies.